Food security through crop diversification in Manipur: Application of Heckman Sample Selection Model - AHEIBAM, MONIKA; SINGH, RAM; FEROZE, SHEIKH MOHAMMAD; CHIPHANG, SINGYALA (The Indian Journal of Agricultural Sciences, 2023)
The paper demonstrates the household food security of crop diversified farm in the state of Manipur. A study was conducted at College of Post Graduate Studies in Agricultural Sciences at Barapani, Meghalaya of Central Agricultural University, Imphal during 2015–16 to 2017–18 by taking two districts namely; Ukhrul and Thoubal selecting one from each region, viz. hill and valley of the state, respectively. A sample of 200 households was drawn by using probability proportional to size. Heckman Sample Selection model was used to analyze the data. The study found that most of the households diversified their crop enterprises which in turn enhanced their household food security by way of consuming own production or generated income helped to purchase food items. Among the factors, namely socio-economic, technological and institutional factors influenced household's decision to diversify crop in the state while determinants of dietary diversity were the age of the household head, family size, extent of crop diversification, non-farm source of income and agricultural income. Hence, the results were indicative of the importance of crop diversification as a viable option in the state for enhanced food security and income of rural smallholders. Hence, wider awareness on crop diversification for realizing its benefits and improving the nutritional status of households in the state of Manipur was the need of the hour.